Explicit and implied significance of contemporary public spaces. Part 2. Alternative spaces - Dziubiński, Dariusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
This paper is a continuation of deliberations on meaning (sense) of public spaces. It refers to unofficial spaces for informal activities, which could be called informal alternative spaces or maybe even a bit exaggeratedly “spaces-of-resistance”. Their extremely important features include absence of control and lack of rules, which distinguish them from other spaces. The paramount advantage visitors gain from these places is the ability to give the space a meaning of their own, thus changing the users’s position from that of a mere user into the user in possession. It also changes his/her relation to the space which ceases to be only a ‘closed object’. It is brought into use, as it is created and linked only for the time of the actor-user's (own) performance. The experimental character of the game leads to a reinterpretation of the meaning (or even necessity to change it) that the space has. Such an approach breaks with the patterns embedded in a collective imaginarium, which promote safe, comfortable behaviours – an unofficial, alternative space must be created each time from scratch, such space is a process. It is not treated as a product, it becomes space of commitment – it becomes political space, but as such, it is a challenge and thus it is interesting only for few people. By meeting each other and being with others we fulfill our basic psychological need, but simultaneously we enter into different roles in a social game in which our own “win” often counts above all. Our private satisfaction can also be valued by a sense of community, collaboration, having something in common, and this obviously can bring benefits to everyone. However, without a deeper thought practices that seek and provide best possible conditions for staying in space can lead to a certain inertia, which can turn into “algorithmization” in satisfying space users, specialized only in passive satisfaction of thoughtless users.